Understanding human resource development : a research-based approach - Mc Goldrick, Jim (Routledge LondonGB, 2002)
Seeks to advance knowledge and understanding of human resource development (HRD). Draws upon the emerging body of research in HRD, primarily UK-based, which provides the underpinning for the conceptual, theoretical and practical advance of HRD.